2018
DOI: 10.1038/s41586-018-0481-8
|View full text |Cite
|
Sign up to set email alerts
|

Precancerous neoplastic cells can move through the pancreatic ductal system

Abstract: Most adult carcinomas develop from noninvasive precursor lesions, a progression that is supported by genetic analysis. However, the evolutionary and genetic relationships among co-existing lesions are unclear. Here we analysed the somatic variants of pancreatic cancers and precursor lesions sampled from distinct regions of the same pancreas. After inferring evolutionary relationships, we found that the ancestral cell had initiated and clonally expanded to form one or more lesions, and that subsequent driver ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
83
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(94 citation statements)
references
References 45 publications
(66 reference statements)
3
83
0
Order By: Relevance
“…Re-review of the histology of the first primary tumor and associated imaging studies did not suggest the presence of a cystic neoplasm. These findings are highly indicative of two independent primary tumors that arose from distinct precursors (38).…”
Section: Resultsmentioning
confidence: 83%
“…Re-review of the histology of the first primary tumor and associated imaging studies did not suggest the presence of a cystic neoplasm. These findings are highly indicative of two independent primary tumors that arose from distinct precursors (38).…”
Section: Resultsmentioning
confidence: 83%
“…Previous reports have suggested that intrapancreatic metastasis may serve as another evolutionary scenario for multiple PDAC . A recent study has suggested that precancerous intraepithelial neoplasms can spread contiguously or disseminate discontiguously along the pancreatic ductal system to form multifocal clonal lesions . Therefore, we hypothesized that two distinct pathways, multicentric carcinogenesis and intrapancreatic metastasis, might contribute to the formation of multiple PDAC.…”
Section: Introductionmentioning
confidence: 93%
“…Similarly, around 33% of humans harbor precursor lesions in their pancreas but the life-time risk of developing pancreatic cancer is 1.6% (NCI Seer 2018; Makohon-Moore and Iacobuzio-Donahue 2016). Hence, most precursor lesions do not progress to cancer within the life-time of humans (Makohon-Moore et al 2018;Lang et al 2020). Because cancer incidence strongly depends on factors such as age, genetic predisposition, life-style, or exposure to mutagens (e.g., sun, smoke, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Martincorena and Campbell 2015;Yokoyama et al 2019;Makohon-Moore et al 2018), and hence DNA shed from these cells can hamper the specificity of a cancer screening test…”
mentioning
confidence: 99%